THE EMERGENCY OF NEGATION EXPRESSIONS IN INTERACTIVE MOTHER-BABY CONTEXTS - Cavalcanti de Almeida, Laís (2019)
Abstract: In this paper, we propose to focus on the emergence of baby denial expressions in interactive contexts through maternal stimuli. To this end, we delimit, to support our sayings Kendon (1982) and McNeill (1985), which relate gestures and speech from the classification of multimodality defining them as a single matrix of meaning, we will also bring other studies that work interactionism under the multimodality look - look, gestures and speech in interaction contexts. For denial, we used the research by Dodane & Massini-Cagliari (2010), Spitz (1998), Beaupoil-Hourdel (2013), Vasconcelos (2017), Barros & Fonte (2016). As for the methodological aspects, this work is longitudinal in nature, that is, to achieve the proposed objective, we analyzed data from a mother-baby dyad (1 to 24 months) through video recordings. Looking at the scenes of interaction between the dyad, we check the baby's various contexts of denials marked throughout life and classify them as: dissatisfaction, rejection, refusal, evasion and prohibition. We conclude by corroborating the importance of denials as an expressive form of the child in the interaction, as they are the first elements that the child uses to show his opinion and position within the interaction.